Electrode material, electrode material preparation method and related sample preparation method

By preparing the LSTNn fuel electrode and converting it into the LSTN-rn fuel electrode through reduction treatment, the problem of structural changes and poor performance of the lanthanum strontium titanium electrode material at high temperatures is solved, and the performance and stability of the electrode material are improved.

CN119542443APending Publication Date: 2025-02-28GUANGDONG POWER GRID CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411717716.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The lanthanum strontium titanium electrode material has problems of slight structural changes and mismatch in thermal expansion coefficients at high temperatures, which affects its electrochemical performance and stability.

Method used

By mixing and grinding and sintering the raw materials including La2O3, SrCO3, TiO2, and NiO according to the pre-designed amount ratio, an LSTNn fuel electrode was prepared, and heated in a reducing atmosphere was converted into an LSTN-rn fuel electrode, and the number of layers n was adjusted to control the micromorphology and performance of the electrode material.

Benefits of technology

The specific surface area, pore structure, conductivity and catalytic activity of the electrode material are improved, and its performance in CO2 electrolysis and fuel cells is enhanced, and its performance in the CO2 electrolysis and fuel cells is enhanced, and it has excellent structural redox stability and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542443A_ABST
    Figure CN119542443A_ABST
Patent Text Reader

Abstract

The invention provides an electrode material, an electrode material preparation method and a related sample preparation method. The electrode material preparation method comprises the following steps: mixing and grinding first raw materials including La2O3, SrCO3, TiO2 and NiO according to a first preset stoichiometric ratio; and sintering to obtain the LSTNn fuel electrode. The preparation method of the electrode material is simple in process, low in cost and low in energy consumption and pollution; the stacked structure of the TiO6 octahedron in the LSTNn material provides more migration paths and precipitation sites for the Ni element, and is beneficial to the performance of the electrode material in CO2 electrolysis, fuel cells and other electrochemical processes; the Ni doping effectively affects the microstructure and the electrochemical performance of the LSTNn; the combined action of the oxygen vacancies and the Ni nanoparticles also promotes the charge transfer process on the surface of the electrode, and improves the conductivity and catalytic efficiency of the electrode), which forms a synergistic effect with the existence of a large number of Ni nanoparticles, and jointly improves the CO2 electrolysis electrochemical activity of the electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid oxide batteries, and in particular to an electrode material, an electrode material preparation method and a related sample preparation method. Background Art

[0002] Solid oxide cells (SOCs) are highly efficient energy conversion devices, and lanthanum strontium titanium (LST) electrode materials, as a potential electrode material for SOCs, have some excellent properties but also some shortcomings. Although lanthanum strontium titanium electrode materials have certain stability at high temperatures, long-term operation in high temperature environments may still cause slight changes in the material structure, thereby affecting its electrochemical performance. The mismatch of the thermal expansion coefficient of the material at high temperatures may also cause interface problems between the electrode and the electrolyte, thereby affecting the overall performance of the battery.

[0003] The component design of lanthanum strontium titanium electrode materials is an important method for modifying high-performance electrode materials. In recent years, domestic and foreign scholars have conducted some research on the modification methods of lanthanum strontium titanium electrode materials. The results show that the ionic conductivity of lanthanum strontium titanium electrode materials is one of the key factors affecting their electrochemical performance. Insufficient ionic conductivity may lead to an increase in the polarization impedance of the battery during the charge and discharge process, thereby reducing the output power and energy efficiency of the battery. Although its ionic conductivity can be improved by doping and other means, there is still room for improvement. The electronic conductivity of the material is also an important factor affecting its electrode performance. Although the electronic conductivity of lanthanum strontium titanium electrode materials is relatively high, it may still not meet the needs of SOCs for high-performance electrode materials under certain conditions. Insufficient electronic conductivity may cause the electron transport of the battery to be blocked during the charge and discharge process, thereby affecting the overall performance of the battery. Summary of the invention

[0004] The main purpose of the present invention is to provide an electrode material, an electrode material preparation method and a related sample preparation method to solve the technical problems of insufficient electrochemical performance and stability of lanthanum strontium titanium electrode materials in the prior art.

[0005] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a method for preparing an electrode material, comprising: mixing and grinding a first raw material including La2O3, SrCO3, TiO2, and NiO according to a first preset metering ratio; and sintering to obtain a LSTNn fuel electrode.

[0006] Furthermore, the mixing and grinding process of the first raw material including La2O3, SrCO3, TiO2, and NiO according to a first preset metering ratio includes: ball milling the first raw material for 1 to 3 hours to obtain a first fine mixed raw material; the sintering process to obtain the LSTNn fuel electrode includes: sintering the first fine mixed raw material at 1300 to 1500°C in an air atmosphere for 8 to 12 hours to obtain the LSTNn fuel electrode.

[0007] Furthermore, the La2O3, the SrCO3, the TiO2, and the NiO are all of analytical grade.

[0008] Furthermore, the sintering of the first finely mixed raw material at 1300-1500° C. in an air atmosphere for 8-12 hours to obtain the LSTNn fuel electrode includes: a heating rate of the sintering treatment is 4-6° C. / min.

[0009] A second aspect of the present invention provides an electrode material, which is prepared by the electrode material preparation method.

[0010] The third aspect of the present invention provides a method for preparing an electrode material sample, comprising: obtaining an LSTNn fuel electrode by adopting the electrode material preparation method; calcining the LSTNn fuel electrode in a first reducing mixed gas to obtain a LSTN-rn fuel electrode with reducing properties.

[0011] Furthermore, the first reducing mixed gas includes 4-6% hydrogen and 94-96% nitrogen.

[0012] Furthermore, the calcining of the LSTNn fuel electrode in the first reducing mixed gas to obtain the reducible LSTN-rn fuel electrode includes: calcining the LSTNn in the first reducing mixed gas at 700-900° C. for 8-12 hours to obtain the LSTN-rn fuel electrode.

[0013] The fourth aspect of the present invention provides a battery preparation method, comprising: sintering YSZ to obtain a YSZ electrolyte pellet; mixing a first binder and a LSTNn fuel electrode prepared by the electrode material preparation method to obtain a LSTNn electrode ink; applying the LSTNn electrode ink to one side of the YSZ electrolyte pellet by screen printing, and calcining to obtain a first YSZ pellet; mixing and grinding a second raw material including La2O3, SrCO3, Co2O3, and Fe2O3 according to a second preset metering ratio, and sintering to obtain a LSCF air electrode; mixing a second binder and the LSCF air electrode to obtain a LSCF electrode ink; applying the LSCF electrode ink to the other side of the YSZ electrolyte pellet by screen printing, and calcining to obtain a LSCF|YSZ|LSTNn battery; calcining the LSCF|YSZ|LSTNn battery in a second reducing mixed gas to obtain a LSCF|YSZ|LSTN-rn battery.

[0014] Furthermore, the first adhesive comprises 95-97% of terpineol and 3-5% of ethyl cellulose; the second adhesive comprises 95-97% of terpineol and 3-5% of ethyl cellulose.

[0015] The electrode material preparation method provided in the first aspect of the present invention comprises the following steps: mixing and grinding a first raw material including La2O3, SrCO3, TiO2, and NiO according to a first preset metering ratio, and sintering the mixture to obtain an LSTNn fuel electrode, which can be used to prepare a fuel electrode for a solid oxide battery. The overall preparation method has a simple process, low cost, less energy consumption, and less pollution. The stacking structure of the TiO6 octahedron inside the LSTNn material will show different arrangements as the number of layers n changes. This structural difference directly affects the distribution of the Ni element inside the material and the difficulty of its precipitation on the surface. Therefore, after the LSTNn fuel electrode is reduced in the subsequent preparation of the battery, if the number of layers n increases, the stacking of the TiO6 octahedron becomes more complex, forming a more diverse crystal structure and channels, thereby providing more migration paths and precipitation sites for the Ni element. That is, by adjusting the number of layers n, the micromorphology and properties of the electrode material, including its specific surface area and pore structure, can be controlled. , conductivity, catalytic activity, etc., which is beneficial to the performance of electrode materials in CO2 electrolysis, fuel cells and other electrochemical processes. For example, in CO2 electrolysis applications, electrode materials with larger specific surface area and higher catalytic activity can more effectively adsorb and convert CO2 molecules, thereby improving electrolysis efficiency and product purity; Ni doping effectively affects the microstructure and electrochemical properties of LSTNn, which increases the concentration of oxygen vacancies in layered perovskites (oxygen vacancies provide more opportunities for the adsorption and activation of CO2 molecules, making CO2 molecules more easily converted into intermediate products, and then undergo subsequent electrolysis reactions. Secondly, Ni nanoparticles, as efficient catalysts, can significantly reduce the activation energy of the reaction and accelerate the reaction rate. The combined action of oxygen vacancies and Ni nanoparticles also promotes the charge transfer process on the electrode surface, improving the conductivity and catalytic efficiency of the electrode), which forms a synergistic effect with the presence of a large number of Ni nanoparticles to jointly enhance the electrochemical activity of the electrode material for CO2 electrolysis.

[0016] The electrode material provided in the second aspect of the present invention, namely the LSTNn fuel electrode, can be used to prepare batteries. The stacking structure of TiO6 octahedrons inside the LSTNn material will show different arrangements as the number of layers n changes. This structural difference directly affects the distribution of the Ni element inside the material and the difficulty of its precipitation on the surface. Therefore, by heating the battery under a reducing atmosphere, the LSTNn fuel electrode is transformed into a reducing LSTN-rn fuel electrode. At this time, if the number of layers n increases, the stacking of the TiO6 octahedrons will become more complex, forming a more diverse crystal structure and channels, thereby providing more migration paths and precipitation sites for the Ni element, that is, by adjusting the number of layers n, the micromorphology and properties of the electrode material, including its specific surface area, pore structure, conductivity, catalytic activity, etc., can be controlled, which is beneficial to the performance of the electrode material in CO2 electrolysis, fuel cells and other electrochemical processes. For example, in CO2 electrolysis applications, electrode materials with larger specific surface area and higher catalytic activity can more effectively adsorb and convert CO2 molecules, thereby improving electrolysis efficiency and product purity; Ni doping effectively affects the microstructure and electrochemical properties of LSTNn, which increases the concentration of oxygen vacancies in layered perovskites (oxygen vacancies provide more opportunities for the adsorption and activation of CO2 molecules, making it easier for CO2 molecules to be converted into intermediate products and then undergo subsequent electrolysis reactions. Secondly, Ni nanoparticles, as efficient catalysts, can significantly reduce the activation energy of the reaction and accelerate the reaction rate. The combined action of oxygen vacancies and Ni nanoparticles also promotes the charge transfer process on the electrode surface, improving the conductivity and catalytic efficiency of the electrode), which forms a synergistic effect with the presence of a large number of Ni nanoparticles to jointly enhance the electrochemical activity of the electrode material for CO2 electrolysis.

[0017] The electrode material sample preparation method provided in the third aspect of the present invention enables the electrode material LSTNn to be converted into the electrode material sample LSTN-rn, so as to facilitate the study and verification of factors affecting the electrochemical properties and stability of the electrode material, such as the structural redox stability of LSTN-rn and the characteristics of LSTN-rn that can increase the paths for oxygen ion migration.

[0018] In the battery preparation method provided in the fourth aspect of the present invention, the LSTNn fuel electrode is prepared by the electrode material preparation method described in the first aspect of the present invention, and the electrode ink is coated on one side of the YSZ electrolyte pellet. The LSCF air electrode is prepared by mixing, grinding and sintering the second raw material, and the electrode ink is coated on the other side of the YSZ electrolyte pellet. Then, the second reducing mixed gas is used for reduction reaction, so that the LSTNn is converted into LSTN-rn. The reducing agent promotes part of the Ti in the LSTNn to 4+ ions are reduced to Ti 2+, promoting the precipitation of Ni elements and the formation of nanoparticles, so that the layered perovskite structure can be retained, and it has excellent structural redox stability. LSTN-rn is sensitive to temperature and is more suitable for use under high-temperature operating conditions. The layered perovskite with an appropriate number of layers can significantly improve the CO2RR performance. The performance stability of the LSTN-rn cathode is improved. The SOEC with the LSTN-rn cathode has a high CO2 generation rate and Faraday efficiency, indicating that LSTN-rn is a potential cathode material for CO2 electrolysis in SOEC; the present invention solves the problem that Ni particles in traditional Ni-YSZ electrodes are prone to agglomeration. The Ni nanoparticles precipitated by in-situ growth in the present invention have strong chemical coupling, and a strong chemical bond is formed between the Ni nanoparticles and the matrix material, which is more stably present on the electrode surface and is not easy to agglomerate, ensuring the high performance of the electrode in the short term, as well as the durability and reliability of long-term operation. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0020] Figure 1 a shows the case where n=5 (La4Sr n-4 ) 0.9 Ti 0.9n Ni 0.1n O 3n+2 Schematic diagram of the crystal structure of layered oxides; Figure 1 b shows the case where n=8 (La4Sr n-4 ) 0.9 Ti 0.9n Ni 0.1n O 3n+2 Schematic diagram of the crystal structure of layered oxides; Figure 1 c shows the case where n=12 (La4Sr n-4 ) 0.9 Ti 0.9n Ni 0.1n O 3n+2 Schematic diagram of the crystal structure of layered oxides; Figure 1 d shows the XRD pattern of LSTNn in the embodiment of the present invention; Figure 1 e and Figure 1 f shows the XRD pattern of LSTN-rn in an embodiment of the present invention; Figure 1 g shows the Raman spectrum of LSTN12 in 5% hydrogen and 95% nitrogen in an embodiment of the present invention; Figure 1 h shows the in-situ high temperature Raman spectrum of LSTN5 in an embodiment of the present invention; Figure 1i shows the in-situ high temperature Raman spectrum of LSTN8 in an embodiment of the present invention; Figure 1 j shows the in-situ high temperature Raman spectrum of LSTN12 in an embodiment of the present invention;

[0021] Figure 2 a shows the H2-TPR curve of LSTN5 in the embodiment of the present invention at 100-900°C; Figure 2 b shows the H2-TPR curve of LSTN8 in the embodiment of the present invention at 100-900°C; Figure 2 c shows the H2-TPR curve of LSTN12 in the embodiment of the present invention at 100-900°C; Figure 2 d shows the SEM image of LSTN-r5 and the distribution diagram of separated Ni nanoparticles in the embodiment of the present invention; Figure 2 e shows the SEM image of LSTN-r8 and the distribution diagram of separated Ni nanoparticles in the embodiment of the present invention; Figure 2 f shows the SEM image of LSTN-r12 and the distribution diagram of separated Ni nanoparticles in the embodiment of the present invention; Figure 2 g shows a high-resolution TEM image of LSTN-r5 in an embodiment of the present invention; Figure 2 h shows a high-resolution TEM image of LSTN-r8 in an embodiment of the present invention; Figure 2 i shows a high-resolution TEM image of LSTN-r12 in an embodiment of the present invention; Figure 2 j shows the EDS image of LSTN-r5 in the embodiment of the present invention; Figure 2 k shows an EDS image of LSTN-r8 in an embodiment of the present invention; Figure 2 1 shows the EDS image of LSTN-r12 in the embodiment of the present invention;

[0022] Figure 3 a shows the XPS spectra of Ti in LSTN5 and LSTN-r5 in the embodiments of the present invention; Figure 3 b shows the XPS spectra of Ti in LSTN8 and LSTN-r8 in the embodiments of the present invention; Figure 3 c shows the XPS spectra of Ti in LSTN12 and LSTN-r12 in the embodiment of the present invention; Figure 3 d shows the XPS spectra of Ni in LSTN5 and LSTN-r5 in the embodiments of the present invention; Figure 3 e shows the XPS spectra of Ni in LSTN8 and LSTN-r8 in the embodiments of the present invention; Figure 3 f shows the XPS spectra of Ni in LSTN12 and LSTN-r12 in the embodiment of the present invention; Figure 3g shows the XPS spectra of O in LSTN5 and LSTN-r5 in the embodiment of the present invention; Figure 3 h shows the XPS spectra of O in LSTN8 and LSTN-r8 in the embodiments of the present invention; Figure 3 i shows the XPS spectra of O in LSTN12 and LSTN-r12 in the embodiments of the present invention;

[0023] Figure 4 a shows the IV curves of SOEC and LSTN-r5 cathode in the embodiment of the present invention at 600-800°C; Figure 4 a shows the IV curves of SOEC and LSTN-r8 cathode in the embodiment of the present invention at 600-800°C; Figure 4 a shows the IV curves of SOEC and LSTN-r12 cathode in the embodiment of the present invention at 600-800°C; Figure 4 d shows the constant energy test data of SOEC and LSTN-r5 cathode in the embodiment of the present invention at different voltages and 800°C; Figure 4 e shows the constant energy test data of SOEC and LSTN-r8 cathode in the embodiment of the present invention at different voltages and 800°C; Figure 4 f shows the constant energy test data of SOEC and LSTN-r12 cathode in the embodiment of the present invention at different voltages and 800°C; Figure 4 g shows the T-ASR curves of SOEC and LSTN-rn (n=5, 8, 12) materials in the range of 600° C. to 800° C. in an embodiment of the present invention; Figure 4 h shows the relaxation time (DRT) distribution diagram of LSTN-rn (n=5, 8, 12) materials in an embodiment of the present invention; Figure 4 i shows the SOEC polarization resistance of the LSTN-rn (n=5, 8, 12) electrode at 800°C in the embodiment of the present invention;

[0024] Figure 5 a shows a stability test data diagram of SOEC and LSTN-r5 in an embodiment of the present invention; Figure 5 b shows the stability test data of SOEC and LSTN-r8 in the embodiment of the present invention; Figure 5 c shows the stability test data of SOEC and LSTN-r12 in the embodiment of the present invention; Figure 5 d shows the production rate of the SOEC electrolysis products and the Faraday efficiency data in the embodiment of the present invention. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0027] The controlled growth of surface nanoparticles is a key factor affecting the electrochemical performance and long-term stability of electrode materials. The in-situ dissolution of lanthanum strontium titanium nanoparticles on the surface can effectively solve the problems of low performance and poor long-term stability, and improve the working performance of electrode materials. However, most of the research on this modification method is based on single and RP structure perovskites, and there is little research on in-situ precipitation of nanoparticles on the surface of other types of perovskites.

[0028] A first aspect of the present invention provides a method for preparing an electrode material, comprising:

[0029] Mixing and grinding the first raw material including La2O3, SrCO3, TiO2 and NiO according to a first preset metering ratio;

[0030] The LSTNn fuel electrode is obtained by sintering. The chemical formula of LSTNn is (La4Sr n-4 ) 0.9 Ti 0.9n Ni 0.1n O 3n+2 ± δ .

[0031] In the chemical formula of LSTNn, taking n=5, 8, 12 as an example, when n=5, its chemical composition precisely corresponds to (La4Sr) 0.9 Ti 4.5 Ni 0.5 O 17±δThis composition ratio ensures that the La, Sr, Ti and Ni elements are combined in a predetermined stoichiometric ratio, while allowing a certain fluctuation in oxygen content (±δ) to reflect the slight deviation that may exist in the actual synthesis process; when n=8, its chemical composition is adjusted accordingly to (La4Sr4) 0.9 Ti 7.2 Ni 0.8 O 26±δ This change not only increases the number of layers, but also leads to corresponding adjustments in the content of each element to maintain the overall stoichiometric balance, and similarly, allows a certain range of fluctuations in the oxygen content; when n = 12, the chemical composition becomes (La4Sr8) 0.9 Ti 10.8 Ni 1.2O37±δ In the sample with this number of layers, the oxygen content is also allowed to fluctuate within a certain range. In the following embodiments, n is taken as n=5, 8, and 12 as examples to facilitate observation of the effects of different n values ​​on material properties. In practical applications, n can be taken as other values, and n=5, 8, and 12 are not used as restrictions on the value of n.

[0032] Combination Figure 1 a to Figure 1 As shown in Figure j, the crystal structure, phase composition and structural changes of LSTNn (n = 5, 8, 12) layered oxides during the reduction process. XRD (X-ray diffraction) and Raman spectroscopy analysis confirmed that LSTNn is a single phase with an orthorhombic structure, and the partial replacement of Ti by Ni did not change its crystal structure. With the increase of n, the XRD peak shifted to a lower angle. Under reducing conditions, nickel precipitation was observed in all LSTN-rn, but the layered perovskite structure was retained, showing excellent structural redox stability. In addition, the departure of oxygen atoms and the precipitation of nickel during the reduction process led to a significant contraction of the lattice parameters. In situ Raman spectroscopy further revealed the changes in the vibration mode of the TiO6 octahedron during the reduction process.

[0033] La2O3, SrCO3, TiO2 and NiO are weighed according to a first preset metering ratio (determined by the corresponding chemical reaction). In order to obtain higher quality products, in this embodiment, La2O3, SrCO3, TiO2 and NiO are preferably of analytical grade, with a purity greater than or equal to 99.8%.

[0034] Furthermore, the mixing and grinding of the first raw material including La2O3, SrCO3, TiO2 and NiO according to a first preset metering ratio comprises:

[0035] Ball milling the first raw material for 1 to 3 hours to obtain a first finely mixed raw material;

[0036] The sintering process is performed to obtain the LSTNn fuel electrode, and the chemical formula of LSTNn is (La4Sr n-4 ) 0.9 Ti 0.9n Ni 0.1n O 3n+2±δ ,include:

[0037] The first finely mixed raw material is sintered in an air atmosphere at 1300-1500° C. for 8-12 hours to obtain the LSTNn fuel electrode.

[0038] Specifically, the first raw material including La2O3, SrCO3, TiO2, and NiO can be pre-mixed by a mixing device, and then put into a ball mill for ball milling for 1 to 3 hours (preferably 2 hours). After fine grinding, the first fine mixed raw material is obtained, and the particle size is significantly reduced, so that each raw material is fully mixed and pre-activated, which is beneficial to subsequent reactions and is more conducive to finally obtaining a LSTNn fuel electrode with uniform structure and excellent performance. After that, the first fine mixed raw material is sintered in an air atmosphere at 1300 to 1500°C (preferably 1400°C) for 8 to 12 hours (preferably 10 hours) to obtain a LSTNn fuel electrode. Optionally, the heating rate of the sintering treatment is 4 to 6°C / min (preferably 5°C / min), so as to ensure that the powder of the first fine mixed raw material can be evenly and slowly heated to the sintering temperature, avoiding excessive internal stress and performance degradation of the material due to excessive heating.

[0039] The electrode material preparation method provided in the first aspect of the present invention comprises the following steps: mixing and grinding a first raw material including La2O3, SrCO3, TiO2, and NiO according to a first preset metering ratio, and sintering the mixture to obtain an LSTNn fuel electrode, which can be used to prepare a fuel electrode for a solid oxide battery. The overall preparation method has a simple process, low cost, less energy consumption, and less pollution. The stacking structure of the TiO6 octahedron inside the LSTNn material will show different arrangements as the number of layers n changes. This structural difference directly affects the distribution of the Ni element inside the material and the difficulty of its precipitation on the surface. Therefore, after the LSTNn fuel electrode is reduced in the subsequent preparation of the battery, if the number of layers n increases, the stacking of the TiO6 octahedron becomes more complex, forming a more diverse crystal structure and channels, thereby providing more migration paths and precipitation sites for the Ni element. That is, by adjusting the number of layers n, the micromorphology and properties of the electrode material, including its specific surface area and pore structure, can be controlled. , conductivity, catalytic activity, etc., which is beneficial to the performance of electrode materials in CO2 electrolysis, fuel cells and other electrochemical processes. For example, in CO2 electrolysis applications, electrode materials with larger specific surface area and higher catalytic activity can more effectively adsorb and convert CO2 molecules, thereby improving electrolysis efficiency and product purity; Ni doping effectively affects the microstructure and electrochemical properties of LSTNn, which increases the concentration of oxygen vacancies in layered perovskites (oxygen vacancies provide more opportunities for the adsorption and activation of CO2 molecules, making CO2 molecules more easily converted into intermediate products, and then undergo subsequent electrolysis reactions. Secondly, Ni nanoparticles, as efficient catalysts, can significantly reduce the activation energy of the reaction and accelerate the reaction rate. The combined action of oxygen vacancies and Ni nanoparticles also promotes the charge transfer process on the electrode surface, improving the conductivity and catalytic efficiency of the electrode), which forms a synergistic effect with the presence of a large number of Ni nanoparticles to jointly enhance the electrochemical activity of the electrode material for CO2 electrolysis.

[0040] A second aspect of the present invention provides an electrode material, wherein the electrode material is prepared by the electrode material preparation method, comprising:

[0041] The first raw material including La2O3, SrCO3, TiO2 and NiO is mixed and ground according to a first preset metering ratio, and sintered to obtain a LSTNn fuel electrode. The chemical formula of LSTNn is (La4Sr n -4) 0.9 Ti 0.9n Ni 0.1n O 3n+2±δ .

[0042] The electrode material provided in the second aspect of the present invention, namely the LSTNn fuel electrode, can be used to prepare batteries. The stacking structure of TiO6 octahedrons inside the LSTNn material will show different arrangements as the number of layers n changes. This structural difference directly affects the distribution of the Ni element inside the material and the difficulty of its precipitation on the surface. Therefore, by heating the battery under a reducing atmosphere, the LSTNn fuel electrode is transformed into a reducing LSTN-rn fuel electrode. At this time, if the number of layers n increases, the stacking of the TiO6 octahedrons will become more complex, forming a more diverse crystal structure and channels, thereby providing more migration paths and precipitation sites for the Ni element, that is, by adjusting the number of layers n, the micromorphology and properties of the electrode material, including its specific surface area, pore structure, conductivity, catalytic activity, etc., can be controlled, which is beneficial to the performance of the electrode material in CO2 electrolysis, fuel cells and other electrochemical processes. For example, in CO2 electrolysis applications, electrode materials with larger specific surface area and higher catalytic activity can more effectively adsorb and convert CO2 molecules, thereby improving electrolysis efficiency and product purity; Ni doping effectively affects the microstructure and electrochemical properties of LSTNn, which increases the concentration of oxygen vacancies in layered perovskites (oxygen vacancies provide more opportunities for the adsorption and activation of CO2 molecules, making it easier for CO2 molecules to be converted into intermediate products and then undergo subsequent electrolysis reactions. Secondly, Ni nanoparticles, as efficient catalysts, can significantly reduce the activation energy of the reaction and accelerate the reaction rate. The combined action of oxygen vacancies and Ni nanoparticles also promotes the charge transfer process on the electrode surface, improving the conductivity and catalytic efficiency of the electrode), which forms a synergistic effect with the presence of a large number of Ni nanoparticles to jointly enhance the electrochemical activity of the electrode material for CO2 electrolysis.

[0043] A third aspect of the present invention provides a method for preparing an electrode material sample, comprising:

[0044] The LSTNn fuel electrode is obtained by adopting the electrode material preparation method;

[0045] The LSTNn fuel electrode is calcined in a first reducing mixed gas to obtain a LSTN-rn fuel electrode having reducing properties.

[0046] In the above-mentioned electrode material sample preparation method, the LSTNn fuel electrode is prepared by the above-mentioned electrode material preparation method, and then the reduced LSTN-rn fuel electrode is obtained by calcining in a first reducing mixed gas (where "r" stands for reduction, thus naming the reduced LSTNn for easy distinction). Further, the first reducing mixed gas includes 4-6% hydrogen and 94-96% nitrogen (preferably 5% hydrogen and 95% nitrogen).

[0047] Furthermore, the LSTNn fuel electrode is calcined in the first reducing mixed gas to obtain a LSTN-rn fuel electrode with reducibility, comprising: calcining the LSTNn in the first reducing mixed gas at 700-900°C for 8-12h to obtain the LSTN-rn fuel electrode (preferably, calcining at 800°C for 10h).

[0048] In this way, through calcination treatment under specific atmosphere, temperature and time, a reducible LSTN-rn fuel electrode, that is, an electrode material sample, is obtained.

[0049] Combination Figure 2 a to Figure 2 As shown in Figure 1, the effect of different n members on the reduction process of LSTNn layered perovskite oxide was investigated by H2-TPR technology. The results show that with the increase of n value, the reduction peak of Ni2+ to Ni0 moves to low temperature, while Ti 4+ To Ti 3+ The broad reduction peak of TiO2 moves to high temperature. A larger n value helps nickel nanoparticles to precipitate at a lower temperature, but 4+ The partial reduction of is hindered by the size of the n perovskite plate. A-site defects can promote B-site precipitation. SEM (scanning electron microscopy) and TEM (transmission electron microscopy) images show that there are a large number of randomly distributed nickel nanoparticles on the surface of the reduced LSTN-rn powder, and as the n value increases, the average diameter of the nanoparticles increases and the aggregation phenomenon becomes more obvious (the average diameter of Ni nanoparticles is about 30-50nm, which is a size that can provide sufficient active sites for catalytic reactions and maintain good structural stability). EDS (energy dispersive spectroscopy) mapping confirmed that these nanoparticles are composed of precipitated metallic nickel, which is consistent with the XRD, TPR and XPS results. In addition, there is a strong interaction between the nanoparticles and the matrix.

[0050] Combination Figure 3 a to Figure 3 As shown in Figure 1, the Ti 2p, Ni 2p and O1s core level spectra of LSTN-rn powders before and after reduction were analyzed by XPS and compared with those of synthesized LSTNn. 3+ / Ti 4+ The mixed state exists, and after reduction, Ti 4+ The ratio is reduced, Ti 3+The oxidation state increases. At the same time, the Ni 2p core energy level changes before and after reduction, and a large amount of Ni0 is precipitated after reduction. The O 1s spectrum shows that the number of lattice oxygen species decreases after reduction, while adsorbed oxygen becomes the main component, indicating a high concentration of oxygen vacancies. In addition, there are more available oxygen ion migration paths in the LSTN-rn layered perovskite oxide under a reducing atmosphere. That is, the conductive behavior of strontium titanate-based perovskite materials strongly depends on the atmosphere during heating, and charge compensation is affected by the defect chemistry of the doped oxide.

[0051] The electrode material sample preparation method provided in the third aspect of the present invention enables the electrode material LSTNn to be converted into the electrode material sample LSTN-rn, so as to facilitate the study and verification of factors affecting the electrochemical properties and stability of the electrode material, such as the structural redox stability of LSTN-rn and the characteristics of LSTN-rn that can allow more paths for oxygen ion migration.

[0052] A fourth aspect of the present invention provides a method for preparing a battery, comprising:

[0053] Sintering YSZ (yttria-stabilized zirconia) (in an air atmosphere, the sintering temperature is 1300-1500° C., preferably 1400° C., and the sintering time is 8-12 hours, preferably 10 hours, so that the YSZ particles are closely combined, which is beneficial to improving the density and ion conduction efficiency of the electrolyte) to obtain YSZ electrolyte pellets;

[0054] Mixing the first binder and the LSTNn fuel electrode prepared by the electrode material preparation method to obtain LSTNn electrode ink;

[0055] Applying the LSTNn electrode ink to one side of the YSZ electrolyte pellet by screen printing, and performing calcination treatment (calcination temperature is 800-1000° C., preferably 900° C., calcination time is 2-4 hours, preferably 3 hours, to remove the binder and enhance the bonding force between the electrode and the electrolyte) to obtain a first YSZ pellet;

[0056] The second raw material including La2O3, SrCO3, Co2O3 and Fe2O3 is mixed and ground according to a second preset metering ratio (including ball milling the second raw material for 1 to 3 hours, preferably 2 hours), and sintered to obtain an LSCF air electrode (including sintering at 1300 to 1500° C. for 8 to 12 hours, preferably sintering at 1400° C. for 10 hours);

[0057] Mixing the second binder and the LSCF air electrode to obtain LSCF electrode ink;

[0058] The LSCF electrode ink is applied to the other side of the YSZ electrolyte pellet by screen printing, and calcined (calcination temperature is 800-1000° C., preferably 900° C., calcination time is 2-4 hours, preferably 3 hours, to remove the binder and enhance the bonding force between the electrode and the electrolyte) to obtain a LSCF|YSZ|LSTNn battery;

[0059] The LSCF|YSZ|LSTNn battery is calcined in a second reducing mixed gas (including calcination at 700-900° C. for 8-12 h, preferably calcination at 800° C. for 10 h, to ensure that the reduction reaction is fully carried out and the Ni element is uniformly precipitated) to obtain a LSCF|YSZ|LSTN-rn battery.

[0060] In the above-mentioned battery preparation method, the first binder comprises 95-97% of pine alcohol and 3-5% of ethyl cellulose; the second binder comprises 95-97% of pine alcohol and 3-5% of ethyl cellulose.

[0061] The first binder and the second binder can both be preferably 96% pine alcohol and 4% ethyl cellulose, which have good solubility and film-forming properties, and are conducive to obtaining uniform and stable LSTNn electrode ink.

[0062] Furthermore, the second reducing mixed gas includes 4-6% hydrogen and 94-96% nitrogen. The second reducing mixed gas is preferably 5% hydrogen and 95% nitrogen, which can provide a reducing and relatively safe environment to avoid oxidation or other adverse reactions at high temperatures.

[0063] Preferably, La2O3, SrCO3, Co2O3, and Fe2O3 in the second raw material are all of analytical grade (purity greater than or equal to 99.8%), and can be dried, ground, and mixed before ball milling to improve the ball milling efficiency and ensure that the raw material purity and particle size meet the requirements.

[0064] In the battery preparation method provided in the fourth aspect of the present invention, the LSTNn fuel electrode is prepared by the electrode material preparation method described in the first aspect of the present invention, and the electrode ink is coated on one side of the YSZ electrolyte pellet. The LSCF air electrode is prepared by mixing, grinding and sintering the second raw material, and the electrode ink is coated on the other side of the YSZ electrolyte pellet. Then, the second reducing mixed gas is used for reduction reaction, so that the LSTNn is converted into LSTN-rn. The reducing agent promotes part of the Ti in the LSTNn to 4+ ions are reduced to Ti 2+, promoting the precipitation of Ni element (migrating from the inside of LSTNn lattice to the surface) and the formation of nanoparticles (Ni migrates to the surface and grows into nano-scale particles in situ), and preparing LSTN-rn layered perovskite oxide modified with Ni nanoparticles as the fuel electrode, whose layered perovskite structure is retained and has excellent structural redox stability. Figure 4 As shown in a to 4i, the IV curve test of CO2RR was carried out by using LSTN-rn as the cathode. The results show that LSTN-rn is sensitive to temperature and is more suitable for use under high temperature operating conditions. The appropriate number of layered perovskites can significantly improve the CO2RR performance (for example, in the constant potential test, the LSTN-r8 cathode has better CO2RR performance in SOEC (solid oxide electrolyzer) and has better electrochemical performance and conductivity). Figure 5 a to Figure 5 As shown in Figure d, a 30-hour stability test was performed on the SOEC with LSTN-rn cathode, and it was found that its performance stability was improved. Analysis of the electrolysis products showed that the SOEC with LSTN-rn cathode had a high CO2 generation rate and Faraday efficiency, indicating that LSTN-rn is a potential cathode material for CO2 electrolysis in SOEC. The present invention solves the problem of easy agglomeration of Ni particles in traditional Ni-YSZ (yttrium-stabilized zirconia) electrodes (which will lead to a reduction in active sites and a decrease in electrode performance). The Ni nanoparticles precipitated by in-situ growth in the present invention have a strong chemical coupling effect, and a strong chemical bond is formed between the Ni nanoparticles and the matrix material, so that they exist more stably on the electrode surface and are not easy to agglomerate, thereby ensuring the high performance of the electrode in the short term, as well as the durability and reliability of long-term operation.

[0065] In addition, combined Figure 4 As shown in Figure 3, DRT analysis reveals the rate-limiting substeps of the electrode reaction and indicates that Peak 2, which is associated with gas conversion and charge transfer, dominates in the LSTN-rn material. The LSTN-r8 material has the best performance due to its appropriate layer number, indicating that the appropriate layer number can promote surface gas conversion and charge transfer even without in-situ grown nanoparticles.

[0066] It should be noted that the use of words such as "first" and "second" to limit corresponding objects is only for the convenience of distinguishing the corresponding objects. Unless otherwise stated, the above words have no special meaning and therefore cannot be understood as limiting the scope of protection of the present invention.

[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an electrode material, characterized in that: include: Mixing and grinding the first raw material including La2O3, SrCO3, TiO2 and NiO according to a first preset metering ratio; The LSTNn fuel electrode is obtained by sintering.

2. The method for preparing an electrode material according to claim 1, characterized in that: The mixing and grinding of the first raw material including La2O3, SrCO3, TiO2 and NiO according to a first preset metering ratio comprises: Ball milling the first raw material for 1 to 3 hours to obtain a first finely mixed raw material; The sintering process to obtain the LSTNn fuel electrode comprises: The first finely mixed raw material is sintered in an air atmosphere at 1300-1500° C. for 8-12 hours to obtain the LSTNn fuel electrode.

3. The method for preparing an electrode material according to claim 1, characterized in that: The La2O3, SrCO3, TiO2 and NiO are all of analytical grade.

4. The method for preparing an electrode material according to claim 2, characterized in that: The LSTNn fuel electrode is obtained by sintering the first finely mixed raw material at 1300-1500° C. in an air atmosphere for 8-12 hours, comprising: The heating rate of the sintering treatment is 4 to 6°C / min.

5. A method for preparing an electrode material sample, characterized in that: include: The LSTNn fuel electrode is obtained by adopting the electrode material preparation method according to any one of claims 1 to 4; The LSTNn fuel electrode is calcined in a first reducing mixed gas to obtain a LSTN-rn fuel electrode having reducing properties.

6. The method for preparing an electrode material sample according to claim 5, characterized in that: The first reducing mixed gas includes 4-6% hydrogen and 94-96% nitrogen.

7. The method for preparing an electrode material sample according to claim 5, characterized in that: The LSTNn fuel electrode is calcined in the first reducing mixed gas to obtain a LSTN-rn fuel electrode having reducing properties, comprising: The LSTNn is calcined in the first reducing mixed gas at 700-900° C. for 8-12 hours to obtain the LSTN-rn fuel electrode.

8. A method for preparing a battery, characterized in that: include: The YSZ is sintered to obtain YSZ electrolyte pellets; The first binder and the LSTNn fuel electrode prepared by the electrode material preparation method according to any one of claims 1 to 4 are mixed to obtain LSTNn electrode ink; Applying the LSTNn electrode ink to one side of the YSZ electrolyte pellet by screen printing, and performing calcination treatment to obtain a first YSZ pellet; The second raw material including La2O3, SrCO3, Co2O3 and Fe2O3 is mixed and ground according to a second preset metering ratio, and sintered to obtain an LSCF air electrode; Mixing the second binder and the LSCF air electrode to obtain LSCF electrode ink; Applying the LSCF electrode ink to the other side of the YSZ electrolyte pellet by screen printing, and calcining to obtain a LSCF|YSZ|LSTNn battery; The LSCF|YSZ|LSTNn battery is calcined in a second reducing mixed gas to obtain a LSCF|YSZ|LSTN-rn battery.

9. The battery preparation method according to claim 8, characterized in that: The first adhesive comprises 95-97% of terpineol and 3-5% of ethyl cellulose; the second adhesive comprises 95-97% of terpineol and 3-5% of ethyl cellulose.

10. An electrode material, characterized in that: The electrode material is prepared by the electrode material preparation method according to any one of claims 1 to 4.